Pengaruh Diversitas Gender Dewan terhadap Kinerja Perusahaan (Studi Global pada berbagai Negara di Dunia) - Natalia, Lita; Arief, Meta; Widyaningsih, Aristanti (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2023)
In this literature, the author reviews board gender diversity in areas related to corporate governance and corporate finance, namely Company Performance globally in various countries in the world. The research method in this article uses a qualitative research approach with the type of research, namely Systematic Literature Review (SLR), where researchers identify and summarise topics related to the main topic, then 24 research articles are selected that are most suitable and used as research samples, as for the subject of the topic mapped in this literature, namely 12 countries in the world. After analysis, the majority of countries in the world, namely Turkey, Ghana, United Kingdom, Greece, Pakistan, Russia, Brazil, India, Indonesia, and Pakistan, state that Board Gender Diversity (BGD) can improve company performance. While in several other countries such as Malaysia, Nigeria, and Latin America, the existence of BGD can reduce company performance.